(untitled) (Revista de História da UEG (REVHIST), 2024)
Leoba was an Anglo-Saxon nun from the eighth century, who joined Boniface in his mission in Frankish territories east of the Rhine. Boniface entrusted Leoba with the leadership of the female monastic community of Tauberbischofsheim, where she established an education center for women and a support station for missionary work. In this paper, we aim to present a general view of the Bonifacian missions and the role of women in them, through a study of Leoba’s career and an analysis of the portrayal of her as a missionary woman in the hagiography Vita Leobae, written in 836 by Rudolf of Fulda. At the end of the eighth century and the beginning of the ninth, there was a strengthening of restrictive ideas concerning the agency of abbesses and nuns outside the monasteries and their coexistence with the opposite sex, which caused an impact on abbesses’ influence and the economies of women ́s communities. In this paper, we analyze how the hagiographer conciliated these ideologies with the memory of a missionary woman, who was a great authority in the time and place in which she lived. Keywords: Hagiography. Gender. Christianization. Missionary Life. Monasticism. Carolingian Period.